2016
DOI: 10.4049/jimmunol.1502193
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Culture of Human Naive and Memory B Cells for Use as APCs

Abstract: The ability to culture and expand B cells in vitro has become a useful tool for studying human immunity. A limitation of current methods for human B-cell culture is the capacity to support mature B-cell proliferation. We have developed a culture method to support the efficient activation and proliferation of both naïve and memory human B cells. This culture supports extensive B-cell proliferation, with approximately 103-fold increases following 8 days in culture, and 106-fold increases when cultures are split … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 99 publications
0
51
0
Order By: Relevance
“…To characterize human B cell repertoires before and after the second tolerance checkpoint (1, 2), we isolated single transitional B cells (CD19 + CD27 -CD38 hi CD10 + IgD + ) and mature, naive B cells (CD19 + CD27 -CD38 lo CD10 -IgD + ) from PBMCs of healthy donors (Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.122551DS1) (23), and cultured individual B cells in Nojima cultures, which support proliferation and plasmacytic differentiation of human B cells (16,17). After 25 days of culture, we harvested culture supernatants containing clonal IgG produced by the differentiated progeny of single transitional or mature B cells and screened them on a panel of foreign and self-antigens (17,24).…”
Section: Single B Cell Cultures Support Robust Proliferation and Igg mentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize human B cell repertoires before and after the second tolerance checkpoint (1, 2), we isolated single transitional B cells (CD19 + CD27 -CD38 hi CD10 + IgD + ) and mature, naive B cells (CD19 + CD27 -CD38 lo CD10 -IgD + ) from PBMCs of healthy donors (Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.122551DS1) (23), and cultured individual B cells in Nojima cultures, which support proliferation and plasmacytic differentiation of human B cells (16,17). After 25 days of culture, we harvested culture supernatants containing clonal IgG produced by the differentiated progeny of single transitional or mature B cells and screened them on a panel of foreign and self-antigens (17,24).…”
Section: Single B Cell Cultures Support Robust Proliferation and Igg mentioning
confidence: 99%
“…To survey for tolerance-induced holes in the human BCR repertoire before and after the second tolerance checkpoint, we cultured single human B cells on stromal cell layers that support B cell proliferation and differentiation to IgG-secreting plasmablasts and plasmacytes (16,17). In this way, we obtained 2331 clonal IgGs from individual transitional and mature B cells representing the BCR repertoires before and after the second tolerance checkpoint (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of human CD40B cells to expand antigen-experienced CD4+ T cells, but also to prime naïve CD4+ T cells was demonstrated in several studies [15, 17, 22, 24, 26, 35, 37, 44, 45]. Lapointe et al [37] showed that when pulsed with tumor lysates, CD40B cells expanded and activated tumor antigen-specific memory CD4+ T cells from the blood of cancer patients.…”
Section: Generation Of Antigen-presenting B Cellsmentioning
confidence: 99%
“…Moreover, activation of lymphocytes by soluble CD40L and anti-TCR-␣␤ antibody alters cell metabolism (30), which can potentially mask the effects of MDV infection on metabolism. Unactivated human or chicken lymphocytes undergo apoptosis in vitro, and only cell activation by various ligands can reduce cell death in lymphocyte culture models (31,32). Therefore, the effects of MDV infection on glycolysis and glutaminolysis were initially studied in CEFs, but these data should be confirmed in immune cells in future studies.…”
Section: Discussionmentioning
confidence: 99%